The determination of solutions of linear differential equations with entire coefficients from their zeros - Asiri, Asim Mohammad Khalid (2012)
This thesis starts from the following observation; if v;w are solutions of y00 + Py = 0 where P is entire, and v and w are both 0 at z0 2 C, then W(v;w) = vw0